Hukum Ekonomi Syariah dan Dampaknya Terhadap Perkembangan Hubungan Bisnis Muslim dan Non-Muslim di Timur Tengah Studi Kasus Uni Emirat Arab - Muhammad Rafi Siregar; Ahmad Rifai; Mariana - (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2022)
The United Arab Emirates is a federation of seven emirates: Ajman, Dubai, Sharjah, Abu Dhabi, um Al-Quwain, Ras Al Khaimah and Emirate of Ras Al Khaimah. The United Arab Emirates is located near the Persian Gulf in the Northeastern part of the Arabian Peninsula; it was founded in 1971 by Sheikh Zayed Al Nahyan. The country's diverse culture and geographic location as a crossroads make it a prime location for commerce and trade. There are currently three emirates in the country: Fujairah, Ras al-Buradj, and Sharjah. Islam plays a crucial role in Gulf culture. Because of this, the role of Islamic principles in dispute resolution and trade is considered a key aspect. This article discusses how Sharia Economic Law affects both Muslim and non-Muslim business relationships in the United Arab Emirates and Dubai. Looking at Law and Development from an Islamic Perspective By addressing the impact of Shariah economic law on economic development, a new vision of legal theory and development is proposed. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//   This page is in English Translate to Indonesian    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate English to IndonesianPRO Never translate English Never translate journal.um-surabaya.ac.id